2021
DOI: 10.35848/1882-0786/ac1981
|View full text |Cite
|
Sign up to set email alerts
|

Improved forward voltage and external quantum efficiency scaling in multi-active region III-nitride LEDs

Abstract: Ultra-low voltage drop tunnel junctions (TJs) were utilized to enable multi-active region blue light emitting diodes (LEDs) with up to three active regions in a single device. The multi-active region blue LEDs were grown monolithically by metal-organic chemical vapor deposition (MOCVD) without growth interruption. This is the first demonstration of a MOCVD grown triple-junction LED. Optimized TJ design enabled near-ideal voltage and EQE scaling close to the number of junctions. This work demonstrates that with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The operation at the lower current density enables the two-junction LED to have higher EQE, and thereby higher WPE than a single-junction LED. This has also been discussed in a few previous paper papers from Akyol et al, and Jamal-Eddine et al 10,12) The use of multiple active regions essentially enables us to achieve higher output power density from the same chip area without sacrificing efficiency.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The operation at the lower current density enables the two-junction LED to have higher EQE, and thereby higher WPE than a single-junction LED. This has also been discussed in a few previous paper papers from Akyol et al, and Jamal-Eddine et al 10,12) The use of multiple active regions essentially enables us to achieve higher output power density from the same chip area without sacrificing efficiency.…”
mentioning
confidence: 79%
“…Tunnel junctions were previously demonstrated for current spreading layers without the use of absorbing indium tin oxide contacts to p-type GaN, 22,23) efficient hole injection into multiple-quantum well active regions, [24][25][26] and cascading of multiple LED active regions. [27][28][29][30] Previous reports of MBE-grown p-down green LED has shown that p-down LEDs grown along Ga-polar direction with well-engineered TJ design can achieve high electrical efficiency owing to the benefits from lowered electrostatic barrier, yet the demonstrated LED suffered from low quantum efficiency due to the induced excess defects from growth condition of the MBE 13) Recently, metalorganic CVD-deposited p-down green LEDs using bottom tunnel junctions with high EQE were demonstrated. 31) Although the demonstrated p-down LED + TJ device showed higher forward voltage drop due to extra voltage penalty at the TJ (caused from the challenges associated with the high Mg doping and its profile in the MOCVD growth), the extracted p-down LED (standalone) forward voltage drop showed that the diode in reversed polarization topology can exhibit lower voltage drop compared to the conventional p-up structure.…”
mentioning
confidence: 99%
“…Conductive and transparent oxides, such as ITO or zinc oxide, are traditionally employed for current spreading layer due to the resistive characteristic of p-type III-nitride materials, yet ITO has greater absorption in blue and UV emissions. TJs not only offer benefit in better optical transparency but also reveal the possibility of the cascade LED design that achieves monolithic integration of multiple emission wavelengths or suppress the efficiency droop issues [37,38]. TJs have been demonstrated by MBE, a hydrogen-free deposition method, and significant improvements in optical efficiency has been shown.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…The variation in the peak wavelengths could be attributed to drift in the growth parameters between the two samples, as also reported previously for visible multi-active region LEDs. 39) In summary, we have demonstrated fully transparent AlGaN tunnel junctions with two multi-active regions in a single device for ultraviolet LEDs accomplished by incorporating lower voltage drop tunnel junctions by a combination of high doping and polarization grading. This proof-of-concept demonstration shows that the performance of UV LEDs can further be improved by well-designed active regions and by increasing the number of multi-junction active regions.…”
mentioning
confidence: 91%
“…Tunnel junctions can enable multi-active region designs with two or more light-emitting regions, which enables high optical power density even at low current density. Previous theoretical 36) and experimental [37][38][39][40][41] reports were limited to visible multi-active region LEDs, and enabled substantial increases in the external quantum efficiency, and output power density while lowering efficiency droop and I 2 R losses, as well as applications such as multiple wavelength emission. 42) There is now a significant body of work on UV LEDs using AlGaN tunnel junctions.…”
mentioning
confidence: 99%